Evaluation of the cost of unused medications in a hospital in Ethiopia: A cross-sectional study - Alem Endeshaw Woldeyohanins; Asmamaw Emagn Kasahun; Chilot Abiyu Demeke; Diriba Demu; Zemene Demelash Kifle (Elsevier, 2022)
Background: In developing countries like Ethiopia one-third of health care expenditure is for medications. However, due to different reasons, patients may not use all the dispensed medications. Thus, the present study aimed to assess the Causes and cost of unused medications at the inpatient setting of the University of Gondar Compressive Specialized Hospital. Methods: A hospital-based cross-sectional study was conducted over two months at University of Gondar Compressive Specialized Hospital. A survey of the Causes and cost of unused medicines was conducted through an interview-guided structured questionnaire in the inpatient setting. Those patients who had unused/leftover medications in the inpatient setting during the study period were the target population. All opened liquid preparations such as vials, ampoules, and bags were excluded from the study since it is tough to calculate the amount leftover/remaining. The collected data were entered with Epi Data version 3.1 and exported to SPSS version 21 for analysis. Descriptive statistics such as standard deviation, percentage, frequency, mean, and median were used for data presentation. Finally, the results were described using texts, tables, and figures. Results: A total of 13 classes of medication were identified during the study period. Among these, antibiotics 74(35.23%) were the most common leftover class of medications with the financial value of 143.48$(25.10%) of total leftover/unused medication. The most common reasons for medication leftover or unused were because of condition resolved 51(24.28%) followed by treatment changed 50(23.8%). Most 86(40.95%) of leftover/unused medication with a monetary value of 5106.80 Ethiopian birr (127.65 USD) was discarded by the patient. About 66(31.43%) of the patients were taken their leftover medication to home for other programs or feature use, 13.80% of patients gave their leftover medications to other patients. More than half 160(76.19%) of unused medications were eligible for use with the monetary value of 17,992.85 (78.7%) Ethiopian birr. Conclusions: Significant amounts of the hospitals' budget were wasted because of unused/leftover medications and have a serious cost impact. Antibiotics were most frequently class of medication leftover/unused and the condition resolved and treatment changed were the two main reasons for medication leftover/unused. Most of the leftover medications were discarded by the patient, only a very limited number of patients/caregivers plan to return their leftover medications to the pharmacy.